Determinants of the continuous operations of micro and small enterprises during COVID-19 pandemic in Ethiopia - Erstu Tarko Kassa (Journal of Innovation and Entrepreneurship, 2021)
The main objective of this study is to assess determinant factors for the continuous operations of micro and small enterprises during COVID-19 pandemic. The study adopted a cross-sectional design, with both descriptive and explanatory research design. To achieve the objectives of the study, 276 respondents were selected from 890 micro and small enterprise owners. The sample of the study was selected through proportional stratified random sampling technique from the business types (manufacturing, construction, urban agriculture, service and trade). To collect the primary data, questionnaires were dispatched to owners/operators of micro and small enterprises. The collected data were analyzed through descriptive, correlation and regression analysis techniques. The finding of the study revealed that people and administrative factors, regulatory factors, economic factors, partnerships, leadership of owner have a positive relationship to micro-small enterprise continuous operations during COVID-19 pandemic with the value of r = 0.457, 0.558, 0.572, 0.519 and 0.654, respectively. The study regression analysis result assured that partnership, economic factors, and leadership of the owner has a positive statistical significant effect on the continuous operations of the micro and small enterprise during COVID-19 pandemic with the value of (p < 0.05). The researcher recommended that strenghtening partnership with stakeloders and excersing best leadership practices are essential to ensure the continuous operations of the micro and small enterpreses.
Keywords: 650; Micro and small enterprises; Continuity; COVID-19; Partnership; Leadership